2014
DOI: 10.18632/oncotarget.2451
|View full text |Cite
|
Sign up to set email alerts
|

A novel action mechanism for MPT0G013, a derivative of arylsulfonamide, inhibits tumor angiogenesis through up-regulation of TIMP3 expression

Abstract: Tissue inhibitors of metalloproteinases 3 (TIMP3) were originally characterized as inhibitors of matrix metalloproteinases (MMPs), acting as potent antiangiogenic proteins. In this study, we demonstrated that the arylsulfonamide derivative MPT0G013 has potent antiangiogenic activities in vitro and in vivo via inducing TIMP3 expression. Treatments with MPT0G013 significantly inhibited endothelial cell functions, such as cell proliferation, migration, and tube formation, as well as induced p21 and cell cycle arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…Abnormal expression of DNMT3B is related to the hypermethylation of the tumor suppressor genes. TIMP3 is an inhibitor of extracellular matrix metalloproteinase that can suppress angiogenesis [ 41 , 42 ], tumor growth [ 43 , 44 ], and invasion and migration [ 43 – 45 ]. It has been reported that in many common tumors, CpG islands of TIMP3 undergo methylation frequently [ 46 , 47 ] and that in the primary tumors, the methylation of the TIMP3 promoter can lead to the loss of its protein expression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of DNMT3B is related to the hypermethylation of the tumor suppressor genes. TIMP3 is an inhibitor of extracellular matrix metalloproteinase that can suppress angiogenesis [ 41 , 42 ], tumor growth [ 43 , 44 ], and invasion and migration [ 43 – 45 ]. It has been reported that in many common tumors, CpG islands of TIMP3 undergo methylation frequently [ 46 , 47 ] and that in the primary tumors, the methylation of the TIMP3 promoter can lead to the loss of its protein expression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous findings, we investigated the arylsulfonamide derivative MPT0G013 as a potent inhibitor of antiangiogenic activities by activating 14, 15. The literature survey indicates that hydroxamic acid contributes to the histone deacetylase (HDAC) inhibition activity through interfering with the binding mode of zinc ion at the catalytic site, and it becomes the symbolic moiety of HDAC inhibitors 16-18.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, HDAC inhibitors are considered as a new type of anti-cancer therapeutics, which show promising results in pre-clinical studies and early phase clinical trials. MPT0G013, a novel HDAC inhibitor, was reported by our colleague to inhibit tumor angiogenesis through up-regulation of TIMP3 expression [ 31 ]. The GI 50 values of MPT0G013 on Hep3B cells and HUVECs are 0.36 μM and 0.14 μM, respectively [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…MPT0G013, a novel HDAC inhibitor, was reported by our colleague to inhibit tumor angiogenesis through up-regulation of TIMP3 expression [ 31 ]. The GI 50 values of MPT0G013 on Hep3B cells and HUVECs are 0.36 μM and 0.14 μM, respectively [ 31 , 32 ]. In the present study, we observed that MPT0G009 exhibits greater potency on cancer cells than HUVECs with the IC 50 values of 0.75 μM and 7.61 μM, respectively.…”
Section: Discussionmentioning
confidence: 99%